2008
DOI: 10.1248/jhs.54.235
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Incorporated into Eggs from Parent Fish Persists for Several Days

Abstract: Chronological changes of bisphenol A (BPA) concentration were investigated for a week in mature medaka (Oryzias latipes) and spawned eggs (embryo) after exposing the fish to BPA at a concentration of 100 µg/l in water. The BPA concentrations in mature fish and spawned eggs increased beginning at the day after initial exposure, and reached an approximately constant level on the second day. On the other hand, the decrease in BPA concentration in the parent body was rapid after being placed back into pure water (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Teleost stress axis functioning is highly conserved, and we have shown previously that the developmental programming of the cortisol stress axis was disrupted by BPA accumulation in eggs in the F1 generation. , To the best of our knowledge, this is the first study to demonstrate BPA impact not only on the plasma stress response but also acute stress-related transcript changes in the liver, muscle, and head kidney of trout in successive generations. The concentrations of BPA reported in trout embryos in the present study are environmentally realistic, as similar BPA concentrations were found in wild fish and zooplankton collected from the BPA-impacted sites. , In addition, recent studies have provided evidence of maternal transfer of BPA from the exposed adult female fish to eggs; , hence, understanding the generational toxicities of maternally deposited BPA is highly relevant from a risk assessment standpoint.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Teleost stress axis functioning is highly conserved, and we have shown previously that the developmental programming of the cortisol stress axis was disrupted by BPA accumulation in eggs in the F1 generation. , To the best of our knowledge, this is the first study to demonstrate BPA impact not only on the plasma stress response but also acute stress-related transcript changes in the liver, muscle, and head kidney of trout in successive generations. The concentrations of BPA reported in trout embryos in the present study are environmentally realistic, as similar BPA concentrations were found in wild fish and zooplankton collected from the BPA-impacted sites. , In addition, recent studies have provided evidence of maternal transfer of BPA from the exposed adult female fish to eggs; , hence, understanding the generational toxicities of maternally deposited BPA is highly relevant from a risk assessment standpoint.…”
Section: Discussionsupporting
confidence: 81%
“…mentally realistic, as similar BPA concentrations were found in wild fish and zooplankton collected from the BPA-impacted sites. 38,39 In addition, recent studies have provided evidence of maternal transfer of BPA from the exposed adult female fish to eggs; 3,6 hence, understanding the generational toxicities of maternally deposited BPA is highly relevant from a risk assessment standpoint.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental exposure to BPS can be more important because there might be no excretion mechanism for BPS in the eggs as suggested for BPA. 33 BPA and related compounds are well-known as weak estrogen agonists. 13,34 However, the results of our study indicate that exposure to BPS is associated with changes of sex hormone regulation in HPG axis, and these changes were unlikely due to the effects of BPS as an ER agonist.…”
Section: Discussionmentioning
confidence: 99%
“…fario ) 5 , 11 , 12 . Moreover, BPA is maternally transferred in fish 13 and this potentially could lead to long-term developmental effects even though the progeny was not exposed to water-borne BPA 14 16 . As BPA may bring about heritable epigenetic modifications 17 , early exposure to BPA may have long-term and multigenerational consequences in fish.…”
Section: Introductionmentioning
confidence: 99%